A Short History of American Industrial Policies - Nester, William R. author. aut Link
V, 329 p.
Keywords: For nearly four centuries, Americans have debated the government's proper role in developing the economy. Some argue that the economy develops the best when government intervenes the least. Others counter that the economy best develops when government and business work together to that end. A Short History of American Industrial Policies analyzes the ideological, political, and industrial policy struggle from the colonial era to the 1990s. To give a complete understanding, both the chronology and process of America's industrial policymaking and policies are explored in depth throughout.